Acceptability of restrictions in the COVID-19 pandemic: a population-based survey in Denmark and Sweden - Nilsen, Per; Seing, Ida; Sekhon, Mandeep; Kallemose, Thomas; Tjørnhøj-Thomsen, Tine; Stefánsdóttir, Nina Thórný; Vrangbæk, Karsten; Andersen, Ove; Kirk, Jeanette Wassar (Frontiers in Public Health, 2023)
Introduction: Denmark and Sweden initially adopted different responses to the COVID-19 pandemic although the two countries share many characteristics. Denmark responded swiftly with many mandatory restrictions. In contrast, Sweden relied on voluntary restrictions and a more “relaxed” response during the first wave of the pandemic. However, increased rates of COVID-19 cases led to a new approach that involved many more mandatory restrictions, thus making Sweden’s response similar to Denmark’s in the second wave of the pandemic. Aim: The aim was to investigate and compare the extent to which the populations in Denmark and Sweden considered the COVID-19 restrictions to be acceptable during the first two waves of the pandemic. The study also aimed to identify the characteristics of those who were least accepting of the restrictions in the two countries. Materials and Methods: Cross-sectional surveys were conducted in Denmark and Sweden in 2021. The study population was sampled from nationally representative web panels in the two countries, consisting of 2619 individuals from Denmark and 2633 from Sweden. The questionnaire captured key socio-demographic characteristics. Acceptability was operationalized based on a theoretical framework consisting of seven constructs and one overarching construct. Results: The respondents’ age and gender patterns were similar in the two countries. A larger proportion of the Swedish respondents had a university education compared with the Danish respondents, but more Danish than Swedish respondents had a vocational education. Low acceptance of the restrictions, defined as being among the 25% with the lowest total score on the seven acceptability statements, was associated with younger age, male gender and lower education levels. Conclusion: Respondents in Sweden were more accepting of the restrictions in the second wave, when the country used many mandatory restrictions. In contrast, respondents in Denmark were more accepting of the restrictions in the first wave than in the second wave, implying an increased weariness to comply with the restrictions over time. There were considerable socio-demographic differences between those who expressed low acceptance of the restrictions and the others in both countries, suggesting the importance of tailoring communication about the pandemic to different segments of the population.